2019
DOI: 10.2147/cmar.s193615
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictors of health care use in Australian cancer patients</p>

Abstract: Objective The purpose of this study is to measure health care utilization in Australian cancer patients based on their demographic, geographic and socioeconomic backgrounds. Method A total of 13,609 participants (aged 15 and over) from 7,230 households were interviewed as part of Wave 13 of the national Household, Income and Labour Dynamics in Australia (HILDA) survey. Five hundred and seventeen participants indicated a current cancer diagnosis with 90% of those receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
(36 reference statements)
1
8
2
Order By: Relevance
“…Studies on gender differences on the utilization of health care have shown that women have higher health care utilization than men [ 39 ]. A 2019 study found that female cancer survivors had more doctor visits and hospital admissions than male cancer survivors [ 60 ]. Prior research has also shown that in women with breast cancer, the most diagnosed type of cancer among women [ 61 ], side-effects of treatments and impairments may persist up to a decade, influencing women’s use of health care services [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on gender differences on the utilization of health care have shown that women have higher health care utilization than men [ 39 ]. A 2019 study found that female cancer survivors had more doctor visits and hospital admissions than male cancer survivors [ 60 ]. Prior research has also shown that in women with breast cancer, the most diagnosed type of cancer among women [ 61 ], side-effects of treatments and impairments may persist up to a decade, influencing women’s use of health care services [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“… There is a need to articulate biomedical health care with sociocultural factors of cancer. Factors such as risk perception, search for care, and patients’ preferences are determinants insofar as these are related to morbidity, severity, survival, and other treatment outcomes in patients with cancer [ 13 , 28 , 29 , 30 ]. The recognition of the relationships between the causal attributions and the adherence of patients to the biomedical treatment may have some implications in patient care, treatment, clinical practice, and public health: health workers identify dimensions that affect the effectiveness of their practices and in the doctor–patient relationship it is necessary to promote person-centered medicine with recognition of sociocultural determinants of cancer; health education-communication can identify strategic issues for patients and relatives; health care must be interprofessional to impact the multidimensionality of the etiology and treatment of cancer; health systems and public health policies must be designed, implemented, and evaluated with the knowledge of the community since their attributions are determinants of the outcomes of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to articulate biomedical health care with sociocultural factors of cancer. Factors such as risk perception, search for care, and patients’ preferences are determinants insofar as these are related to morbidity, severity, survival, and other treatment outcomes in patients with cancer [ 13 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52][53] There are many reasons to interpret existing data as evidence of surgical underuse for patients with lower income, particularly in the US, where employer-based insurance is common. [54][55][56][57] At the same time, there is growing concern that at least part of wealth-based differences in utilization may represent overuse of certain treatments that are at best unnecessary and at worst harmful. 4,30,[58][59][60][61] If this is the case, residents of higher-income neighborhoods may be at increased risk of unnecessary or harmful care.…”
Section: Discussionmentioning
confidence: 99%
“…Single-country studies have demonstrated that wealthier patients are likelier to obtain cancer screening, undergo cardiovascular procedures, and receive cardiac transplants; there are few studies on this topic outside the US . There are many reasons to interpret existing data as evidence of surgical underuse for patients with lower income, particularly in the US, where employer-based insurance is common . At the same time, there is growing concern that at least part of wealth-based differences in utilization may represent overuse of certain treatments that are at best unnecessary and at worst harmful .…”
Section: Discussionmentioning
confidence: 99%